2D Metal‐Organic Framework Derived Co3O4 for the Oxygen Evolution Reaction and High‐Performance Lithium‐Ion Batteries. Issue 12 (3rd November 2020) - Zheng, Hao‐Yan; Xie, Dan; Li, He; Wu, Shuang‐Yu; Qin, Bo‐Wen; Cui, Zheng; Zhang, Xiao‐Ying; Zhang, Jing‐Ping
Abstract: Recently, MOF‐derived (metal‐organic framework) 2D materials, due to the special structure of the MOF inherited, have become a potential candidate for application in energy storage and conversion. In this work, a new 2D layered Co−MOF was synthesized as the precursor for fabricating Napoleon‐like Co3 O4 (NL−Co3 O4 ). The monolayer thickness of NL−Co3 O4 is approximately 70 nm. The unique structure of layered porous of NL−Co3 O4 derived from Co−MOF plays an important role in improving electrochemical and electro‐catalysis properties. As lithium ion battery anode material, NL−Co3 O4 shows out‐bound cycling performance and rate capacity, which has an unprecedented high reversible capacity of 1120.5 mA h g −1 at 200 mA g −1 after 300 cycles and high rate capacities of 579.4 mA h g −1 under the current density of 6.4 A g −1 . NL−Co3 O4 still exhibits capacity of 679 and 576 mA h g −1 after 200 cycles at high current densities of 1 and 4 A g −1, respectively. Moreover, NL−Co3 O4 has efficient oxygen evolution reduction (OER) catalytic performance (overpotential, ca. 420 mV), comparable with commercial RuO2 . During the process of continuous catalysis of OER, NL−Co3 O4 shows good durability for about 15 h. Abstract : Layered porous NL−Co3 O4 derived from Co−MOF exhibits an enhanced electrochemical performance for lithium‐ion batteries and oxygen evolution reaction.